Pengaruh Karakteristik Pemerintah Daerah dan Laporan Hasil Pemeriksaan Terhadap Kinerja Keuangan - Isna Aeni Latifah; Dewi Amalia (Universitas Muhammadiyah Jember, 2022)
Government financial performance is an illustration of the level of achievement of financial management on the implementation of a program/activity in realizing the goals, objectives, vision, and mission that contained in the regional government strategic plan. The purpose of this study was to examine the effect of the characteristics of local governments, namely regional size, intergovernmental revenue, regional expenditures, legislative measures, and audit reports in the form of audit findings and audit opinions on the financial performance of local governments. The data used in this study is secondary data sourced from the website djpk.kemenkeu.go.id, the website bpk.go.id, and the websites of each local government. The sample in this study was district and city governments in Indonesia that selected using a purposive sampling technique based on specified criteria. The data collection technique used a documentation study, then the data was analyzed using multiple linear regression analysis. The results of this study indicate that the size of the local government, regional spending, and the size of the legislature affect the financial performance of local governments. Meanwhile, intergovernmental revenue, audit findings, and audit opinions have no effect on the financial performance of local governments.